2014
DOI: 10.1016/j.cma.2013.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Post-buckling nonlinear static and dynamical analyses of uncertain cylindrical shells and experimental validation

Abstract: The paper presents a complete experimental validation of an advanced computational methodology adapted to the nonlinear post-buckling analysis of geometrically nonlinear structures in presence of uncertainty. A mean nonlinear reduced-order computational model is first obtained using an adapted projection basis. The stochastic nonlinear computational model is then constructed as a function of a scalar dispersion parameter, which has to be identified with respect to the nonlinear static experimental response of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 47 publications
0
39
0
Order By: Relevance
“…This would imply that the linear mistuning would be considered by extracting the random linear part from random matrix [K], keeping the nonlinear quadratic and cubic terms as deterministic terms for the nonlinear calculations. Nevertheless, this case has been investigated in [7] in the context of the post-buckling nonlinear dynamical analysis of an uncertain cylindrical shell. With such method, a strong nonlinear level of uncertainty δ N L K = 0.45 yielded an equivalent linear uncertainty level δ L K = 0.025 for the linear part of the structure, yielding a subsequent scale effect, preventing to distinguish any differences between the linear and nonlinear uncertainty cases.…”
Section: Difficulties About Quantifying Nonlinear Mistuning With Respmentioning
confidence: 99%
See 3 more Smart Citations
“…This would imply that the linear mistuning would be considered by extracting the random linear part from random matrix [K], keeping the nonlinear quadratic and cubic terms as deterministic terms for the nonlinear calculations. Nevertheless, this case has been investigated in [7] in the context of the post-buckling nonlinear dynamical analysis of an uncertain cylindrical shell. With such method, a strong nonlinear level of uncertainty δ N L K = 0.45 yielded an equivalent linear uncertainty level δ L K = 0.025 for the linear part of the structure, yielding a subsequent scale effect, preventing to distinguish any differences between the linear and nonlinear uncertainty cases.…”
Section: Difficulties About Quantifying Nonlinear Mistuning With Respmentioning
confidence: 99%
“…Solving the stochastic nonlinear equations in the time-domain with efficient algorithms based on the arc-length methods [7,8] All the details concerning the theoretical construction of such methodology and its application to a large finite element model of an industrial bladed-disk can be found in [8].…”
Section: Computational Modeling Of Mistuning Uncertaintiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several works have been published concerning experimental validation of the nonparametric probabilistic approach of both the computational model-parameter uncertainties and the model uncertainties induced by modeling errors (e.g., [96,[106][107][108][109][110][111]). …”
Section: Hyperparameter Of the Stochastic Reduced-order Model (Srom) mentioning
confidence: 99%